Karakterisasi Bobot Jenis dan Identifikasi Kalsium Pada Susu Kedelai - Bart Agus Raya; Hadi Kurniawan; Fajar Nugraha (State University of Gorontalo, 2023)
Soy milk is a drink that is good for health because it contains protein, unsaturated fatty acids, vitamins, carbohydrates and important minerals needed by the body such as calcium. Calcium functions to help the process of forming bones and teeth, blood clotting, muscle contraction, transmitting nerve cell signals, maintaining bone density, supplements in lowering LDL cholesterol levels. This study aims to determine the density characteristics of soy milk produced and to identify the calcium content qualitatively in soy milk drinks circulating in Pontianak City. The research method used in this study is descriptive non-experimental using 3 samples of soy milk circulating in Pontianak City with purposive sampling technique. Sample preparation in this study was carried out by wet digestion using HNO3 65% p.a solvent. Qualitative identification of calcium content was carried out using 5% ammonium oxalate reagent. The presence of a white precipitate after the addition of 5% ammonium oxalate indicates a positive calcium in the sample. Characterization of the specific gravity of soy milk was carried out using a pycnometer. The results obtained in this study are samples of soy milk A, B and C are positive for calcium because they form a white precipitate when soy milk samples are added with 5% ammonium oxalate reagent and the density of soy milk A, B and C is 1, respectively. ,00894905 g/mL, 1.008108836 g/mL and 1.008789684 g/mL.